“Civilizing Nature” in Australian Painting - Zhang, Chunyan (Advances in Social Sciences Research Journal, 2022)
In Australian paintings and literary works of the colonial period, the wilderness and the Aboriginal people were represented as natural hurdles to be crossed and overcome, elements to be struggled against by the colonists who were attempting to “appropriate the environment exclusively to a British agenda of ‘civilization’ .” [1] This is manifestation of the Darwinian evolutionary rhetoric, the idea that societies progress from hunter-gatherer to Western industrialism in a linear hierarchy. This theme is prevalent in paintings and literature. Establishing this narrative was of paramount importance to the white settlers. It can be seen principally in the motif of “civilizing nature”, in which depictions of labour (images of the actual work of taming the wild landscape) or leisure (images of this work completed in the idyllic landscape) are stressed. This motif plays out the colonial agenda of celebrating masculine control over natural forces.